Mapping the Musamus University Campus Using the Bm Tie Point at Mopah Merauke Airport - Yance Kakerissa (Global Writing Academica Researching and Publishing, 2022)
Musamus University is one of the state universities located in the easternmost region of the archipelago, which is currently under construction. In the current era of development, the availability of maps is something that cannot be left behind, especially for the physical development of facilities and infrastructure, as progress in the field of science and technology is so rapid. Measurement and mapping work is an integral part of civil engineering work planning or building design. This writing needs to be done in order to provide correct information, the presence of information will be used to plan something. Likewise, mapping vehicles can not only be carried out terrestrially, but also photogrammetrically, and even propagate in space with satellite technology with various advantages. Each vehicle has advantages and disadvantages so it really depends on the mapping, the level of detail of the objects that must be presented, and the coverage of the area to be mapped. And the methodology that the author uses in this study is the Literature methodology and the Observation Methodology. Surveys and mapping were carried out on the Musamus University campus and its supporting infrastructure, the results of the calculation are as follows: top thread = 1550m, middle thread = 1300m, bottom thread = 1050m, optical distance = 50m, flat distance = 49.98m, height difference = 1.51m and angle correlation = 0 1’26’’